On a pseudo-Volterra nonhomogeneous integral equation - Kosmakova, M.T.; Akhmanova, D.M.; Tuleutaeva, Zh.M.; Kasymova, L.Zh. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In this paper the issues of the solvability of a pseudo-Volterra nonhomogeneous integral equation of the second kind are studied. The solution to the corresponding homogeneous equation and the classes of the uniqueness of the solution are found in [1]. By replacing the right-hand side and the unknown function, the integral equation is reduced to an integral equation, the kernel of which is not ¾compressible¿. Using the Laplace transform, the obtained equation is reduced to an ordinary first-order differential equation (linear). Its solution is found. By using the solution of the homogeneous equation the form of a particular solution of the nonhomogeneous differential equation is defined (by the variation method of an arbitrary constant). By using the inverse Laplace transform, a particular solution of the pseudo-Volterra nonhomogeneous integral equation under study is obtained. The case of an nonhomogeneous integral equation with the value of the parameter k = 1 is considered and studied. Classes for the right side and the solution of the integral equation are indicated.
Біртекті емес псевдо-Вольтерра интегралдық теңдеуі туралы
Об одном псевдо-Вольтерровом неоднородном интегральном уравнении
Keywords: pseudo-Volterra nonhomogeneous integral equation; class of essentially bounded functions; inverse Laplace transformation; residue